Visibilidade eleitoral: uma análise do enquadramento das revistas semanais sobre a candidatura de Heloísa Helena nas eleições presidenciais de 2006 - Gonçalves, Nathalia Augusta (Universidade Federal de São Carlos, 2010)
The present study aims to discuss how women who are candidates for political office are represented in the media. In this way, we intend to perform a study that makes an intersection between three topics: gender, media and politics. The current literature has demonstrated that women who are candidate to political office have been under represented in the media. It is presupposed that the media has a great importance for the formation of political capital of those who desire to organize their carriers to reach the highest political office, that is, the Presidency. Therefore, it becomes indispensable to analyze how the candidates image is frequently presented in the media. In the present study, this will be done by focusing on the gender and analyzing the framework undertaken by the main Brazilian weekly news magazines on the candidacy of Heloisa Helena in the presidential elections in 2006.
Keywords: Eleições; Mídia; Gênero; Política; CIENCIAS HUMANAS::CIENCIA POLITICA